2019
DOI: 10.1002/14651858.cd012819.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative epidural analgesia versus systemic analgesia for thoraco-lumbar spine surgery in children

Abstract: Postoperative epidural analgesia versus systemic analgesia for thoraco-lumbar spine surgery in children (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…7 When the combination of opioids and local anaesthetics is used in epidural analgesia, it has a significant synergistic effect, which can enhance the analgesic effect, prolong the analgesic time, reduce the concentration and dosage of local anaesthetics, and improve patient satisfaction. 8 However, the combination of opioids and local anaesthetics may be also complicated with many side effects. Previous studies 9,10 have reported that the combined use may cause side effects such as nausea and vomiting, skin itching and urinary retention, which are poorly tolerated by patients.…”
mentioning
confidence: 99%
“…7 When the combination of opioids and local anaesthetics is used in epidural analgesia, it has a significant synergistic effect, which can enhance the analgesic effect, prolong the analgesic time, reduce the concentration and dosage of local anaesthetics, and improve patient satisfaction. 8 However, the combination of opioids and local anaesthetics may be also complicated with many side effects. Previous studies 9,10 have reported that the combined use may cause side effects such as nausea and vomiting, skin itching and urinary retention, which are poorly tolerated by patients.…”
mentioning
confidence: 99%
“…The regulatory agencies in France have enforced 'Jardé law,' an improved clinical trial directive that enhances the protection of the rights of trial participants 71 . Clinical trials involve special population groups like the children, pregnant women, and elderly aged, among other vulnerable groups, which may potentially pose ethical and legal obligations (Figure 5) [72][73][74][75][76] .…”
Section: Human Participants In Clinical Trialsmentioning
confidence: 99%
“…Adults (≥ 18 years) who underwent elective cervical or thoracolumbar spine surgery and required hospital admission for at least 24 hours were included. Exclusion criteria included receiving intraoperative intrathecal or postoperative epidural analgesia (previously shown to provide significant improvement in postoperative pain intensity compared with placebo 12,13 ), admission to the intensive care unit, spine surgery for acute trauma, concurrent cervical and thoracolumbar surgeries, more than one surgery performed on the same day, and fewer than 2 postoperative numeric rating scale (NRS) pain evaluations recorded in the first 24 hours. Preemptive analgesia and intraoperative local anesthetic use were not standardized.…”
Section: Entry Criteriamentioning
confidence: 99%